Bayesian model averaging using power-expected-posterior priors - Dimitris Fouskakis; Ioannis Ntzoufras (Econometrics, 2020)
This paper focuses on the Bayesian model average (BMA) using the power-expected-posterior prior in objective Bayesian variable selection under normal linear models. We derive a BMA point estimate of a predicted value, and present computation and evaluation strategies of the prediction accuracy. We compare the performance of our method with that of similar approaches in a simulated and a real data example from economics.
Keywords: 330; Bayesian model averaging; Bayesian variable selection; expected-posterior priors; imaginary training samples; power-expected-posterior priors